Improving Mathematical Understanding Ability Using Tournament Learning with the Help of Panta Media - Shofia Aina Rahmani; M. Maulana; I. Isrokatun (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2024)
Students' understanding of mathematical concepts is still relatively low, especially in data material. One of them is caused by the learning process which is still student-centered. So this research aims to find out how to increase student's ability to understand mathematical concepts using tournament-based learning with the help of panta media. This type of research is quasi-experimental with a nonequivalent control group research design. The population used was class V students in North Sumedang District with research samples from class V at SDN Sindang II as the experimental class and SDN Jatihurip as the control class. The instrument used is a test of the ability to understand mathematical concepts with description questions. The analysis technique in this research is the mean difference test (paired sample t-test and independent sample t-test) which has been tested for normality and homogeneity. To determine the increase in students' mathematical abilities, the N-Gain test was carried out. The two classes were given different treatments, namely the experimental class with tournament-based learning assisted by panta media and the control class with conventional learning. The increase in students' ability to understand mathematical concepts can be seen from the average N-Gain results in the experimental class of 0.6500 in the moderate improvement category and in the control class of 0.2591 which is classified as low improvement. The two classes have significant differences in their ability to understand mathematical concepts. It was concluded that tournament-based learning with the help of panta media can improve students' understanding of mathematical concepts.